Redescription of Pelecorhynchus kroeberi (Lindner), a Patagonian species rediscovered after more than 100 years in Chile (Diptera: Pelecorhynchidae) - González, Christian Raúl; Elgueta, Mario (Papéis Avulsos de Zoologia, 2022)
An adult female of Pelecorhynchus kroeberi (Lindner, 1925) is newly recollected after more than 100 years and it is herein redescribed, including, for the first time, illustrations of genitalia. The specimen was collected in the Región de Aysén, Provincia de Aysén (46°40′11.9″S, 74°00′54.0″W), in the extreme south of Chile, and the specimen is deposited in the Entomological Collection of Museo Nacional de Historia Natural, Santiago, Chile.